A Protocol for a Comprehensive Monitoring and Evaluation Framework With a Compendium of Tools to Assess Quality of Project ECHO (Extension for Community Healthcare Outcomes) Implementation Using Mixed Methods, Developmental Evaluation Design - Ghosh, Smita; Roth, Brenna M.; Massawe, Irene; Mtete, Emmanuel; Lusekelo, Jacob; Pinsker, Eve; Seweryn, Steven; Moonan, Patrick K.; Struminger, Bruce B. (Frontiers in Public Health, 2021)
The United States Centers for Disease Control and Prevention (CDC), through U.S. President’s Emergency Plan for AIDS Relief (PEPFAR), supports a third of all people receiving HIV care globally. CDC works with local partners to improve methods to find, treat, and prevent HIV and tuberculosis. However, a shortage of trained medical professionals has impeded efforts to control the HIV epidemic in Sub-Saharan Africa and Asia. The Project Extension for Community Healthcare Outcomes (ECHO) model expands capacity to manage complex diseases, share knowledge, disseminate best practices, and build communities of practice. This manuscript describes a practical protocol, evaluation framework, and compendium of tools to assess quality of implementation and monitor improvement. The mixed-methods developmental evaluation using an appreciative inquiry approach includes a survey, focus group discussion guides, semi-structured interview guides, and readiness assessments. In addition, ECHO session content will be objectively reviewed for accuracy, content validity, delivery, appropriateness, and consistency with current guidelines. Finally, we offer a mechanism to triangulate data sources to assess acceptability and feasibility of the evaluation framework and compendium of monitoring and evaluation tools. Expected impact of the study on public health: • A unique process to engage diverse group of stakeholders using an appreciative inquiry (change management) process to co-create a comprehensive evaluation framework and a compendium of assessment tools. •The participatory process and developmental evaluation methodology was used to co-create data collection tools for both quantitative and qualitative data to assess implementation.